A structured professional development curriculum for postdoctoral fellows leads to recognized knowledge growth - Steen, Kaylee; Vornhagen, Jay; Weinberg, Zara Y.; Boulanger-Bertolus, Julie; Rao, Arvind; Gardner, Margery Evans; Subramanian, Shoba (PloS one, 2021)
Postdoctoral training enables research independence and professional readiness. National reports have emphasized professional development as a critical component of this training period. In response, many institutions are establishing transferable skills training workshops for postdocs; however, the lack of structured programs and an absence of methods to assess outcomes beyond participant satisfaction surveys are critical gaps in postdoctoral training. To address these shortcomings, we took the approach of structured programming and developed a method for controlled assessment of outcomes. Our program You 3 (You, Your Team, Your Project), co-designed by postdoctoral fellows, focused on discussing specific management and leadership skills agnostic of ultimate career path(s) in a structured manner. We then measured outcomes in a controlled manner, by systematically comparing perceived knowledge and growth as indicators of awareness and confidence in participants against that of non-participants as the control group. You 3 participants self-rated greater growth in targeted competencies compared to non-participants independent of the number of years of training. This growth was shown by multiple criteria including self-reporting and associative analysis. Correspondingly, You 3 participants reported greater knowledge in 75% of the modules when compared to controls. These data indicate that structured learning, where postdocs commit to a curriculum via a cohort-structure, leads to positive outcomes and provides a framework for programs to assess outcomes in a rigorous manner.